An Extended Special Issue on Advances in High-Performance Fiber-Reinforced Concrete - Chao-Wei Tang (Applied Sciences, 2023)
Adding fiber to cement concrete can improve the shortcomings of concrete, such as low tensile properties and low ductility, and improve its resistance to permeability and impact [...]